Artificial Intelligence for Marketing: Systematic Literature Review - Dianti, Annisa Rahma; Mualifah, Teti; Dirgantara, I Made Bayu (LifeSciFi, 2024)
This journal performs a Systematic Literature Review on Artificial Intelligence (AI) in marketing and its impact on various business aspects, innovation, and customer engagement. Artificial Intelligence in marketing refers to the combination of data analytics, machine learning and automation in marketing strategies to enhance decision-making, personalization, and consumer experiences. Currently, the rapid advancement of technology has heightened public interest in Artificial Intelligence applications, encouraging companies to adopt AI-driven marketing practices. This journal systematically reviews the literature related to Artificial Intelligence in marketing, focusing on its impact on business performance, efficiency, and customer interaction. The literature review utilizes the Watase Uake Website, initially gathering 143 articles published from 2019 to 2024, from which 57 journals were analyzed using specific criteria. This journal serves as a valuable resource for the development of future research, particularly in the areas of Artificial Intelligence applications in marketing and their implications for business and consumer engagement.